EFFECT OF MICROSYMBIONTS ON THE ABILITY OF VAGINAL EPITHELIOCYTES TO MODIFY BIOLOGICAL PROPERTIES OF BACTERIA - E. A Kremleva; A. V Sgibnev; S. V Cherkasov (Журнал микробиологии, эпидемиологии и иммунобиологии, 2015)
Aim. Study regularities of effects of various types of vaginal microsymbionts on the ability of mucosal epitheliocytes of the vagina to modify biological properties of bacteria. Materials and methods. Effect of thermo-inactivated cells of Staphylococcus aureus, Escherichia coli, H2O2-producing and H2O2-nonproducing lactobacilli on the ability of primary vaginal epitheliocytes to alter growth and antagonistic activity of Staphylococcus aureus, Escherichia coli, H2O2-producing and H2O2-nonproducing lactobacilli was studied using a multicomponent module system. Results. Alterations of composition of vaginal epitheliocyte exometabolites under the effect of S. aureus and E. coli was established to result in a pronounced stimulation of antagonistic activity of H2O2-producing and an increase of the number of H2O2-nonproducing lactobacilli. Thermo-inactivated cells oflactobacilli stimulated production of metabolites by epitheliocytes, that suppress the growth and antagonistic activity of allochthonous microflora and stimulate similar parameters of lactobacilli. The strongest effects on the ability of vaginal epitheliocytes to alter biological properties of bacteria were rendered by H2O2-producing lactobacilli. Conclusion. The regularities identified allow to examine epitheliocytes and normoflora of vagina as a symbiotic system, the coordinated interaction of its components is directed on maintaining microecological stability of female reproductive tract.